Where is meaning when form is gone? Knowledge representation on the Web - Terrence A. Brooks (Information Research: An International Electronic Journal)
This essay argues that legacy methods of knowledge represenation do not transfer well to a Web environment. Legacy methods assume discrete documents that persist through time. Web documents are often products of dynamic scripts, database manipulations and caching or distributed processing. The size and rate of growth of the Web prohibits labor-intensive methods such as manual cataloging. This essay suggests that an appropriate future home of content-bearing metadata is extensible markup technologies. Meaning can be incorporated in Extensible Markup Language (XML) various ways such as semanticaly rich markup tags, attributes and links among XML sources.